Developing Asian local currency bond markets: Why and how? - Mark M. Spiegel (Asian Development Bank Institute (ADBI), 2009)
This paper examines the motivation for, and the success of, regional efforts in Asia to promote local currency bond markets. The analysis demonstrates that Asian local currency bond markets made substantial gains as a region going into the current global financial crisis. However, we argue that the current financial crisis requires a reassessment of the merits of promoting local currency bond markets and the gains that have been made to date. While most of the initial motivations for encouraging the development of domestic local currency bond markets appear to remain valid, there are some exceptions. However, the degree to which success in the development of these markets will be sustained remains unknown until global financial markets regain tranquility and official interventions into these markets are removed.
Keywords: F36; G15; G20; G28; 330; Internationale Anleihe; Wechselkursrisiko; Rentenmarkt; Finanzmarktkrise; Kapitalmarktliberalisierung; Asien